UJI KELAYAKAN SEDIAAN TEBAL TANPA HEMOLISIS UNTUK DIAGNOSIS Plasmodium falciparum di LABORATORIUM AKADEMI ANALIS KESEHATAN 17 AGUSTUS 1945 SEMARANG - Kusumawati, Dyah; Fiscarina, Ika Theresia (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2018)
Background: The case of malaria in the eastern part of Indonesia requires considerable consideration in the process of making thick blood stocks. The current procedure, use hemolysis techniques. The process of removal in the malaria survey takes longer time before the preparation can be examined. The thickness of different thick blood sections causes the time for the release varies. A new microscopic observation can show whether a thick dosage without hemolysis is feasible to be used as a support for malaria diagnosis which is a gold standard. Eligibility includes the core of old violet blood cells, usually not visible granules, only eosinophil granules. Platelets are mauve and often in groups. Parasites appear small, cytoplasmic boundaries are often unreal. Ring shape often appears as